Occurrence rate of whistler waves in the magnetotail reconnection region. Issue 7 (6th July 2017) - Huang, S. Y.; Yuan, Z. G.; Sahraoui, F.; Fu, H. S.; Pang, Y.; Zhou, M.; Fujimoto, K.; Deng, X. H.; Retinò, A.; Wang, D. D.; Yu, X. D.; Li, H. M.
Abstract: It has long been suggested that whistler waves play an active role during magnetic reconnection. However, all previous observations were based on case studies and could not give a detailed picture as to where the whistler waves occur in the reconnection region. In this paper, a statistical study by using the Cluster data is performed to investigate the spatial distribution and the occurrence rate of whistler waves in the magnetotail reconnection region. It is found that the occurrence rate of the whistler waves is large in the separatrix region (| B x / B 0 | > 0.4) and in the pileup region (| B x / B 0 | < 0.2, | θ | > 45°, where θ  = arctan( B z / B x )), but is very small in the vicinity of the X ‐line. These statistical results are well consistent with recent kinetic simulations and with previous observational case studies. Key Points: Occurrence rate of the whistler waves is revealed in reconnection region Occurrence rate is large in the separatrix and pileup region, but low in the X ‐line region Statistical results are well consistent with the previous case study and kinetic simulations